RESILIENSI PENDIDIKAN PEREMPUAN DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - M. Fadli; Sabaruddin (Universitas Muhammadiyah Prof Dr Hamka, 2020)
The equality of the rights of men and women is not only in a career in the world of work during, but more importantly in the review of Islamic philosophy is the equal right to education both religious and general education. The purpose of this article is to examine how the resilience of women's education in the philosophy of Islamic education. This study uses a literature review approach, first the author examines how the resilience of women's education then views of some Muslim philosophers on women's education. Furthermore, it examines the role and position of women, the verses of the Koran that deal with the role of women, children's education and women's education and women's public space in the perspective of Islamic education philosophy. This article concludes that in Islam every Muslim male and female are required to know about aqeedah, halal and haram and other legal issues, so that the position of women is equal to men in obtaining teaching with the provisions that they must be able to maintain their nature as Muslim women and there are no restrictions in getting more knowledge for women than that Islam gave them the right to learn in the same opportunities as men, even the Prophet Muhammad gave permission for them to go out to prepare their future on condition that they should cover their genitals.